Enhancing Wheat Growth with Integrated Nutrient Management in Agroforestry Systems - Prakash; Pant, K. S.; Prakash, Prem; Bhatia, Avinash Kumar; Saakshi (International Journal of Economic Plants, 2024)
The study was carried out during month of November to April in the year, 2021–2023 at Majhgoan Farm, Department of Silviculture and Agroforestry, Dr. Y. S. Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh (173 230), India with the aim of evaluating the impact of integrated nutrient management (INM) and different planting conditions on the growth and yield of wheat under Grewia optiva. The experiment involved eight treatments combining organic and inorganic manures under two planting conditions, replicated three times in a randomized block design (RBD) with a factorial arrangement. The results indicated that both planting conditions and nutrient sources significantly influenced wheat growth and yield. Specifically, wheat grown in open conditions (S2), when supplemented with 50% Recommended Dose of Fertilizers (RDF) and 50% Farm Yard Manure (FYM), demonstrated superior vegetative growth and yield attributes. Among the treatments, T5 (50% RDF+50% FYM) was identified as the most effective for improving bio–economic performance in a wheat+Grewia optiva agroforestry system. The study recommends adopting the T5 nutrient management strategy in open planting conditions for cost-effective and enhanced wheat production in Grewia optiva Drummond–based agroforestry systems. These findings provide valuable insights for optimizing wheat cultivation in agroforestry settings, with potential benefits for the economic sustainability of farming in the region. Therefore, by adopting the agroforestry model consisting Grewiaoptiva+wheat, farmers can lead to good economic as well as ecological returns.